Long-Lasting Amelioration of Walking Trajectory in Neglect after Prismatic Adaptation - Rabuffetti, Marco; Folegatti, Alessia; Spinazzola, Lucia; Ricci, Raffaella; Ferrarin, Maurizio; Berti, Annamaria; Neppi-Modona, Marco (Frontiers in Human Neuroscience, 2013)
In the present investigation we explored the effect of prismatic adaptation (PA) applied to the upper right limb on the walking trajectory of a neglect patient with more severe neglect in far than in near space. The patient was asked to bisect a line fixed to the floor by walking across it before and after four sessions of PA distributed over a time frame of 67 days. Gait path was analysed by means of an optoelectronic motion analysis system. The walking trajectory improved following PA and the result was maintained at follow-up, fifteen months after treatment. The improvement was greater for the predicted bisection error (estimated on the basis of the trajectory extrapolated from the first walking step) then for the observed bisection error (measured at line crossing). These results show that PA may act on high level spatial representation of gait trajectory rather than on lower level sensory-motor gait components and suggest that PA may have a long lasting rehabilitative effect on neglect patients showing a deviated walking trajectory.